2014
DOI: 10.1556/abiol.65.2014.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ascorbic acid on some physiological changes of pepino (Solanum muricatumAit.) under chilling stress

Abstract: In this study, the changes caused by chilling stress on some physiological parameters of pepino (Solanum muricatum Ait.) plant and the effects of ascorbic acid (100 mM) applied exogenously on these changes were examined. For this purpose, the photosynthetic pigments (chlorophyll a, chlorophyll b, total chlorophylls and carotenoids), ascorbic acid, total phenolic compounds, malondialdehyde and proline contents in leaves of pepino taken on 5 th and 10 th days were determined. As a result of chilling stress, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…TPC significantly enhanced in lettuce leaf basil exposed to 6 °C 13 . Sivaci et al 31 demonstrated the association of plant response to stress stimuli with the levels of phenolic compounds. A substantial increments in soluble phenolic concentrations have been also indicated in tomato and watermelon plants grown in chilling conditions.…”
Section: Discussionmentioning
confidence: 99%
“…TPC significantly enhanced in lettuce leaf basil exposed to 6 °C 13 . Sivaci et al 31 demonstrated the association of plant response to stress stimuli with the levels of phenolic compounds. A substantial increments in soluble phenolic concentrations have been also indicated in tomato and watermelon plants grown in chilling conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As such, enzymatic and non‐enzymatic protective mechanisms have been reported for the scavenging of the over‐generated ROS under oxidative stress. The activities of antioxidative enzymes such as superoxide dismutase and ascorbate peroxidase have been shown to be increased for detoxifying ROS in Lens culinaris seedlings at 40–45 °C treatment, and antioxidative compounds such as ascorbic acid (AsA) protected Solanum muricatum seedlings from oxidative stress at 10 °C . Exploring the changing mechanism of crops under high and low temperature stress is therefore meaningful for enhancing yield and production.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the main effects ( p ≤ 0.001) proved that low temperature generally increased the content of malondialdehyde in both sage cultivars (Table 1). Preliminary results did not confirm such a relationship in sage [26]; however, Sivaci et al [17] described an increase in MDA content in chilled pepino plants in comparison to the control. Overall, our findings showed that overproduction of MDA occurred on the 12–14th day of chilling treatment.…”
Section: Resultsmentioning
confidence: 93%
“…Cheng et al [13] described similar patterns of glutathione and ascorbate concentration changes in watermelon plants up to the 3rd day of chilling, but later, the ascorbate content remained stable, while the glutathione content increased until the 7th day. Sivaci et al [17] showed an increase in ascorbic acid and total phenolics content between the 5th and 10th day of chilling of pepino, while the level of carotenoid compounds decreased on the 5th day in comparison to control plants and then their concentration was similar to the control. Proietti et al [18] did not find significant changes in ascorbate content between chilled and control spinach on the 2nd day of chilling, but later it started to rise and reached the maximum after seven days, with a 41% increase with respect to control leaves.…”
Section: Introductionmentioning
confidence: 99%